2013
DOI: 10.1152/ajprenal.00127.2012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 1 receptor resistance to blockade in the opossum proximal tubule cell due to variations in the binding pocket

Abstract: Blockade of the angiotensin (ANG) II receptor type 1 (AT(1)R) with angiotensin receptor blockers (ARBs) is widely used in the treatment of hypertension. However, ARBs are variably effective in reducing blood pressure, likely due, in part, to polymorphisms in the ARB binding pocket of the AT(1)R. Therefore, we need a better understanding of variations/polymorphisms that alter binding of ARBs in heterogeneous patient populations. The opossum proximal tubule cell (OKP) line is commonly used in research to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Since Olmesartan was crystalized in the AT 1 R (PDB: 4ZUD) [ 7 ], which served as our starting structure, and was the focus of our previous studies [ 20 ], we first docked Olmesartan back into the apo-AT 1 R model described above ( S1 File ). Three docking programs were utilized: AutoDock 4.2 ( Fig 4A ), AutoDock Vina ( Fig 4B ), and MOE ( Fig 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Since Olmesartan was crystalized in the AT 1 R (PDB: 4ZUD) [ 7 ], which served as our starting structure, and was the focus of our previous studies [ 20 ], we first docked Olmesartan back into the apo-AT 1 R model described above ( S1 File ). Three docking programs were utilized: AutoDock 4.2 ( Fig 4A ), AutoDock Vina ( Fig 4B ), and MOE ( Fig 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Ang II binding to AT1R is key to downstream signaling that activates intracellular second messengers and gene regulation ( Hunyady and Catt, 2006 ). Given the lack of specificity of AT1R antibodies, we used radiolabeled Ang II which is more robust and sensitive to the receptor expression ( Herrera et al, 2013 ; Nistala et al, 2013 ; Ogola et al, 2018 ). Ang II can bind to both AT1R and AT2R, and our previous studies consistently demonstrated that 2ME2 specifically downregulates AT1R and not AT2R without impacting the affinity of Ang II to the receptors ( Koganti et al, 2014 ; Ogola et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reactivity of NHE3 dependent on Ang II was also confirmed. Although RPTEC/TERT1 cells are an immortalised RPTEC cell line prepared using only TERT1 and are commercially available, this cell line has not been characterised regarding AT1R signalling 54,55 . Hence, our ciRPTEC will provide an alternative resource for immortalised RPTEC and could be used to analyse other proximal tubule-related proteins in addition to ATRAP.…”
Section: Discussionmentioning
confidence: 99%